Hambatan Implementasi Manajemen Berbasis Sekolah di SMAN 8 Rejang Lebong - Hamengkubuwono Hamengkubuwono; Eli Susanti (STAI Ma'had Aly Al-Hikam Malang, 2021)
School-based management emerged as a solution to achieve equal distribution of educational needs in accordance with the context of each school. This study conducted a case study to reveal the obstacles faced by SMAN 8 Rejang Lebong in implementing the school-based management. All parts of SMAN 8 Rejang Lebong from leadership components, teachers, staffs, to students were involved as the informants who were selected purposively to provide the required data. Data were collected using interviews and observations which were then triangulated and analyzed using an interactive model. The findings revealed several obstacles in the application of school-based management, namely: first, curriculum management had been implemented properly, but student learning achievements were still not optimal. Second, the management of Educators and Education ahd been carried out, but the implementation was not optimal. Third, student management had been carried out, but funding for student activities was still lacking. Fourth, financial management had been carried out, but finances were too limited. Fifth, improvement in the management of facilities and infrastructure had been carried out, but it had not been able to support learning achievement. Sixth, the school had carried out the management of school and community relations, but the communication had not been established as expected.